AB0008 Lack of Association between Polymorphisms in Interlukin (IL-12, IL-12R, IL-23, IL-23R Genes and Takayasu Arteritis in A Chinese Population. (15th July 2016) - Yang, K.-Q.; Yang, Y.-K.; Wen, D.; Meng, X.; Zhang, Y.; Jiang, X.-J.; Wu, H.-Y.; Zhang, H.-M.; Song, L.; Bian, J.; Zhou, X.-L.
Abstract : Background: Takayasu arteritis (TA) is a chronic inflammatory arteritis with unknown cause. Genetic components may play an important role in the pathogenesis of TA. It is indicated that HLA-B*52 allele contributes to TA development worldwide. IL12B is identified as a susceptibility gene for TA in two recent genome-wide association studies. To date, several loci in the genes coding for members of the IL-12/IL-23 pathway have been found to be involved in the pathogenesis of various immune-mediated diseases. Objectives: The goal of this study was to investigate the relationship between polymorphisms in interleukin (IL)-12, IL-12R, IL-23, and IL-23R genes and TA in a Chinese population. Methods: A case-control study was performed to investigate the associations of nineteen single nucleotide polymorphisms (SNPs) mapping to IL12A, IL12B, IL12RB1, IL12RB2 and IL23R with susceptibility to TA in 145 Chinese TA patients and 300 healthy controls. Genotype identification was performed with the MassARRAY system from Sequenom. In addition, HLA-B*52 genotypes were detected by the polymerase chain reaction using the sequence-specific primers (PCR-SSP).The statistical analysis was conducted by chi-square test and unconditional Logistic regression with plink. Results: No significant differences were found for the distribution of allele and genotype frequencies of these SNPs between TA patients and healthy controls. However, a trend for IL12A rs582054 and IL23R rs1004819 in association with the TA phenotype was detected. TA patients carrying the rs582054/ rs568408 haplotype ( P c =0.019) appeared less likely to progress to a more severe form of disease. And the C allele ( P c =0.082) of IL23R rs1004819 appeared to be a protective factor to refractory disease. The association of TA with HLA-B*52 was confirmed in this cohort of Chinese patients. Whereas, there was no interaction between HLA-B*52 and polymorphisms in IL-12/IL-23 axis genes. Conclusions: These findings suggest that the polymorphisms of IL12A, IL12B, IL12RB1, IL12RB2 and IL23R might make no contribution to the susceptibility of TA in the Chinese population. References: Terao C. Revisited HLA and non-HLA genetics of Takayasu arteritis-where are we? J Hum Genet. 2015. doi: 10.1038/jhg.2015.87. Terao C, Yoshifuji H, Kimura A et al. Two susceptibility loci to Takayasu arteritis reveal a synergistic role of the IL12B and HLA-B regions in a Japanese population. Am J Hum Genet. 2013; 93:289–97. Saruhan-Direskeneli G, Hughes T, Aksu K et al. Identification of multiple genetic susceptibility loci in Takayasu arteritis. Am J Hum Genet. 2013; 93:298–305. van Wanrooij RL, Zwiers A, Kraal G, Bouma G. Genetic variations in interleukin-12 related genes in immune-mediated diseases. J Autoimmun. 2012; 39:359–68. Duvallet E, Semerano L, Assier E, Falgarone G, Boissier MC. Interleukin-23: a key cytokine in inflammatory diseases. Ann Med. 2011;43:503–11. Disclosure of Interest: None declared